Representasi Perempuan dalam Novel Cerita Calon Arang Karya Pramoedya Ananta Toer - Rahman, Ifa Hanifa; Rizkasari, Elinda (Ruang Kata, 2024)
Representation of women in the Calon Arang novel by Pramoedya Ananta Toer. This study aims to reveal the differences between angel and monster in the novel Calon Arang Story by Pramoedya Ananta Toer. This research is in the form of descriptive qualitative with data sources in the form of the novel Calon Arang. This study uses data analysis methods. The results of the study found the differences between angels and monsters and the representation of women in the novel Calon Arang. Calon Arang in this novel is portrayed as creepy with an evil nature. Other figures are described as angels with perfect physical images. The portrayal of angels and monsters triggered by Braidoti illustrates that there is a patriarchal goal to perpetuate the beautiful standard of perfect physical form recognized by society.